Early structural brain development in infants exposed to HIV and antiretroviral therapy in utero in a South African birth cohort. Issue 1 (18th January 2022) - Wedderburn, Catherine J.; Groenewold, Nynke A.; Roos, Annerine; Yeung, Shunmay; Fouche, Jean‐Paul; Rehman, Andrea M.; Gibb, Diana M.; Narr, Katherine L.; Zar, Heather J.; Stein, Dan J.; Donald, Kirsten A.
Abstract: Introduction: There is a growing population of children who are HIV‐exposed and uninfected (HEU) with the successful expansion of antiretroviral therapy (ART) use in pregnancy. Children who are HEU are at risk of delayed neurodevelopment; however, there is limited research on early brain growth and maturation. We aimed to investigate the effects of in utero exposure to HIV/ART on brain structure of infants who are HEU compared to HIV‐unexposed (HU). Methods: Magnetic resonance imaging using a T2‐weighted sequence was undertaken in a subgroup of infants aged 2–6 weeks enrolled in the Drakenstein Child Health Study birth cohort, South Africa, between 2012 and 2015. Mother–child pairs received antenatal and postnatal HIV testing and ART per local guidelines. We compared subcortical and total grey matter volumes between HEU and HU groups using multivariable linear regression adjusting for infant age, sex, intracranial volume and socio‐economic variables. We further assessed associations between brain volumes with maternal CD4 cell count and ART exposure. Results: One hundred forty‐six infants (40 HEU; 106 HU) with high‐resolution images were included in this analysis (mean age 3 weeks; 50.7% male). All infants who were HEU were exposed to ART (88% maternal triple ART). Infants who were HEU had smaller caudate volumes bilaterally (5.4% reduction, p < 0.05) compared to HU infants. There were no group differences in other subcortical volumes (all p > 0.2). Total grey matter volume was also reduced in infants who were HEU (2.1% reduction, p < 0.05). Exploratory analyses showed that low maternal CD4 cell count (<350 cells/mm 3 ) was associated with decreased infant grey matter volumes. There was no relationship between timing of ART exposure and grey matter volumes. Conclusions: Lower caudate and total grey matter volumes were found in infants who were HEU compared to HU in the first weeks of life, and maternal immunosuppression was associated with reduced volumes. These findings suggest that antenatal HIV exposure may impact early structural brain development and improved antenatal HIV management may have the potential to optimize neurodevelopmental outcomes of children who are HEU.